PERANAN PROGRAM MODEL KAWASAN RUMAH PANGAN LESTARI (M-KRPL) TERHADAP PENINGKATAN PENDAPATAN RUMAH TANGGA DI KABUPATEN SIAK - Iskandar, Muhamad; Edwina, Susy; Khaswarina, Shorea (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The Sustainable Food House Area Model Program is a government’s program to fulfill the household nutrition and increase income by taking advantage from yard as farming area. This research aim to know the rate of increment household groups income before and after the program held, know the contribution M-KRPL program towards household groups income and know the problems that faced by farmer. Random sampling methode was the sampling technique that was used in this research which in accordance to the number of respondens were 42 samples in Siak Regency. Data were analyzed using farm income analysis, contribution analysis and t-test analysis. Based on the result, income before and after the program has been able to increase revenue and provide benefits to the group in Siak. The results of t-test showed that there was significance among groups activities to strive for M-KRPL program toward household income. Natural factors, techniques to overcome pests and disease, technology and capital were be problem that farmer faced. Keywords: M-KRPL program, household income, revenue